Diagnostic features of a chronic immunosuppressive viral process in a cat suspected of feline infectious peritonitis: a clinical case from veterinary practice - Tkachyvskyi, S.; Galatiuk, O.; Romanishina, T.; Lakhman, A. (Scientific Progress & Innovations, 2025)
The article presents a clinical case of a chronic immunosuppressive viral process in a mixed-breed cat born in 2014, showing oral cavity lesions, anorexia, and dysphagia. The investigation was conducted stepwise during 2024 at the veterinary clinic «Vet Center» («Vet+Klinika», Irpin, Ukraine). The diagnostic protocol included clinical examination, haematological and biochemical blood tests, enzyme-linked immunosorbent assay (ELISA), and polymerase chain reaction (PCR). Immunological and molecular-genetic tests were performed at the «BALT» laboratory (Kyiv, Ukraine). Haematological analyses were carried out using automated haematology and biochemistry analysers (Micro-20Plus and HTI BioChem FC-120). Clinical observations indicated a prolonged chronic inflammatory process in the oral cavity. A moderate leukocytosis with neutrophilic predominance (80,6 %), relative lymphopenia (3,0 × 10⁹/L), and signs of viral suppression of the megakaryocytic lineage and systemic immunodeficiency (P-LCR 9,9 %) were recorded. The biochemical profile revealed a combination of renal dysfunction markers (creatinine – 273,5 μmol/L, urea – 15,2 μmol/L) and pronounced disturbances in lipid (cholesterol – 7,36 mmol/L) and enzymatic metabolism (ALT – 51,2 U/L, AST – 21,9 U/L, amylase – 4547,5 U/L). Serological testing (ELISA) detected antibodies against feline coronavirus structural proteins, indicating a prolonged persistence of infection. Subsequent molecular-genetic examination (PCR) of samples from the upper respiratory tract mucosa was positive for feline calicivirus antigen, regarded as a co-infectious factor capable of enhancing immuno-inflammatory responses and contributing to the development of feline infectious peritonitis (FIP). Thus, the diagnosis of calicivirosis did not exclude but rather confirmed the key role of immunosuppression in the disease pathogenesis. The obtained results allowed the case to be interpreted as a probable dry form of FIP complicated by calicivirus co-infection. This clinical case highlights the importance of comprehensive diagnostic approaches and the recognition that severe co-infections often serve as markers of an underlying immunosuppressive state associated with FIP.